Effects of subsidy policies on smallholder coconut sector: a preliminary exposition - Zulkifly Hj. Mustapha, (Universiti Kebangsaan Malaysia, 1981)
The coconut smallholder development programme involve substantial public sector development expenditure through the provision of subsidies, grants and other facilities. The subsidies and grants are intended as a support in terms of production incentive towards increased production and income for coconut smallholders. In addition, as a government policy, it is also aimed to provide protection to the smallholder production.